Peran Guru BK dalam Mengatasi Konflik Interpersonal Siswa di Lingkungan Sekolah SMP SWASTA Eria Medan - Akhir Pardamean Harahap; BPI-C Uinsu 17 (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
Guidance and counseling teachers have the role of guiding students outside of lessons. Guidance and Guidance Teachers are responsible for student behavior at school and are responsible for assisting the development and welfare of students, especially at the adolescent stage. Adolescence is a time full of conflict. This period is called a period of change, changes in the body, behavior patterns, and roles expected by social groups, and is a period of searching for identity to elevate oneself as an individual. In relation to interpersonal relationships, sometimes one individual has several differences between one individual and another, such as differences in opinions, goals, needs, desires and hopes. This can trigger interpersonal conflicts in students. This research uses qualitative research with observation and interview methods. The results of this research state that the role of guidance and counseling teachers is to provide individual services to students who have problems and this is very effective to do because it is an effort made directly to the individual.